Spousal influence and assortative mating on time preferences: a field experiment in the USA - Gnagey, Matthew; Grijalva, Therese; Rong, Rong (Review of economics of the household, 2020)
Households make economic tradeoffs over time. We seek to understand how a spouse’s individual time preference influences joint household decisions. We conduct a field experiment with 94 pairs of couples in the United States. Each subject makes a series of choices between payoffs received at two different times for oneself and then jointly with their spouse as a household. Results from our sample indicate that husbands do not have more influence than their wives do on the joint decision. This finding differs from previous conclusions drawn from data collected in developing countries. We further find that differences in education, age, and earned income do not provide spouses with additional bargaining power. However, the relative power shifts based on individual preferences related to patience, savings, risk tolerance, and which spouse controls the household income. Lastly, our data supports assortative mating based on time preferences, but we do not find evidence supportive of spousal socialization, spousal selection, or changing matching patterns on time preferences.